Transcriptome and Metabonomics Combined Analysis Revealed the Defense Mechanism Involved in Hydrogen-Rich Water-Regulated Cold Stress Response of Tetrastigma hemsleyanum - Liu, Yuxiu; Pan, Junjie; Ni, Sui; Xing, Bincong; Cheng, Kejun; Peng, Xin (Frontiers in Plant Science, 2022)
The poor cold resistance has become the bottleneck problem of Tetrastigma hemsleyanum (T. hemsleyanum) planting industry. Exogenous hydrogen (H2) plays an important role in improving plant stress resistance. However, the key factors and regulatory network of plant in response to hydrogen-rich water (HRW) treatment under environmental stress are not clear. Here, we conducted integrative analyses of metabolome and transcriptome profile to reveal the defense mechanism involved in HRW-regulated cold stress response of T. hemsleyanum. The application of 75% HRW could alleviate stress damage by decreasing stomatal apparatus density, as well as significantly increase photosynthetic efficiency and mitigate physiological indexes of resistance, such as Pn, Cond, MDA, SOD, etc., which were changed by cold stress. A total of 7883 DEGs and 439 DEMs were identified. DEGs were the most relevant to phenylpropanoid, isoflavonoid, monoterpenoid, and flavonoid biosynthesis pathway. Using gene co-expression analysis (WGCNA), we identified one gene module showed a strong correlation with total antioxidant capacity and transpiration rate. Trend analysis indicated that phenylpropanoid biosynthesis pathway played major roles in the transcription and metabolism process of HRW treatment under cold stress. Based on the integrated analysis of genes and metabolites, the results showed cold stress up-regulated the expression of PAL, CHS, COMT, CCR, F3H, etc., resulting in the accumulation of coniferyl alcohol and eriodictyol contents in T. hemsleyanum under cold stress, but the 75% HRW treatment could attenuate the enhancement. The study not only identified the main strategy of HRW protection against cold stress, but also provided candidate genes for flavonoid biosynthesis, so as to better improve cold tolerance through molecular breeding.